Effects of glazing and chitosan-based coating application on frozen salmon preservation during six-month storage in industrial freezing chambers - Soares, Nuno M. (2015)
Freezing and glazing are techniques commonly used to reduce the incidence of fish deterioration processes. In order to find an alternative to complement freezing and replace water glazing, the present work aimed at evaluating the effect of water glazing and edible coatings of 0.5% w/v and 1.5% w/v chitosan on quality parameters of frozen fish. Both types of coatings - water glazing and chitosan coatings - were applied directly on frozen Atlantic salmon (Salmo salar) and stored for 9 months at -22 °C. Several parameters such as coating/glazing loss, weight loss, drip loss, Total Viable Counts (TVC), Total Volatile Basic-Nitrogen (TVB-N), K-value, pH and color coordinates L*a*b* were periodically evaluated in order to compare glazing with the chitosan-based coatings and uncoated control samples. Samples coated with 1.5% w/v chitosan performed better in maintaining the color of the salmon and controlling microbial contamination of frozen and thawed samples.